Land use change and forest management affect soil carbon stocks in the central hardwoods, U.S - Nave, Lucas E.; DeLyser, Kendall; Domke, Grant M.; Holub, Scott M.; Kabrick, John M.; Keller, Adrienne B.; Leopold, Patricia; Peters, Matthew P.; Solarik, Kevin A.; Swanston, Christopher W. (Geoderma Regional, 2025)
Most research addressing land use change and forest management effects on soil carbon (C) is conducted at large or localized scales, rather than intermediate scales where management is planned and implemented. We assessed effects of land use and forest management on soil C stocks, for the Central Hardwoods ecoregion of the U.S., using meta-analysis, soil survey and national forest inventory databases to examine baseline controls on soil C stocks and their responses to land use and forest management. Biotic and geologic factors drive baseline variation in soil C stocks across the ecoregion, with forest type and productivity being most important in surface horizons and parent material dominating at the whole profile level. Among forest management treatments, prescribed fire is most noteworthy, decreasing O horizons to an extent determined by place and practice (mean: −53 %). Coal mine reclamation is extensive in the region, and while there is no effect of forest vs. herbaceous reclamation, distinct overburden types have different effects on soil C stocks (mean: +183 %). Land use change effects on soil C are difficult to determine due to the preferential use of the most favorable soils for agriculture, the relegation of forests to the least productive soils, and the tendency for reforestation to occur on marginal soils. Overall, our results can help forest managers anticipate the C outcomes of typical burn prescriptions in this region of extensive prescribed fire, and help landowners and planners understand how parent material and soil properties influence soil C stocks under agriculture and mine reclamation.